Pengembangan Teknologi Informasi Geografi sebagai Media Eksplorasi Keanekaragaman Hayati (Biodiversitas) di Indonesia - Suryana, I Putu Gede Eka; Antara, I Gede Made Yudi (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
Indonesia is a country with the second-highest terrestrial biodiversity wealth in the world. When combined with marine biodiversity, Indonesia is the first (source). The loss of biodiversity will have profound implications not only for the environment. The key to the development of the Indonesian nation and state in the future lies in efforts to advance science and technology and make it the backbone of sustainable development. Sustainable development is all efforts to improve the quality of human life. One form of technology that can support the preservation of biodiversity or biodiversity is a geographic information technology (TIG). The use of TIG applications can be in the form of mapping the distribution biodiversity or as a form of monitoring so the condition of the biodiversity can be seen from time to time. The forms of TIG are Remote Sensing, Geographic Information Systems, and GPS. Therefore, this research method is carried out by reviewing or interpreting written materials based on the context. The material can be published notes, textbooks, articles, and the like related to the TIG. An example of a TIG study for biodiversity exploration is knowing the existence of forest resources. Utilization of remote sensing for forest monitoring with satellite remote sensing (Spaceborne Sensing). Satellite remote sensing uses satellites as vehicles to carry sensors for earth sensing.